The Fraction of Carbon in Soil Organic Matter as a National‐Scale Soil Process Indicator - Reinsch, Sabine; Lebron, Inma; de Jonge, Lis Wollesen; Weber, Peter L.; Norgaard, Trine; Arthur, Emmanuel; Gomes, Lucas; Pesch, Charles; Konstantinos, Karyotis; Zalidis, George; Epelde, Lur; Romic, Marija; et al. (Wiley-Blackwell, 2025)
Soil organic matter (SOM) is an important component of ecosystem carbon stocks. Generally, SOM found in mineral and organo-mineral soils can be categorised into two fractions: particulate organic matter (POM) and mineral-associated-organic matter (MAOM), both of which contain soil organic carbon (SOC). Understanding the relationship between SOC and SOM fractions provides insight into SOM decomposition and SOC storage potential. Here we show an intriguingly tight relationship between the fraction of SOC in SOM (denoted as fOC), habitat and soil physical properties, as well as SOC stored in POM and MAOM. This opens up new ways to predict spatial variations in the distribution of POC and MAOC using more widely available fOC data as a covariate. By compiling 14 datasets and 9503 measurements from across Europe and globally we analysed fOC across mineral and organic soils, which fell between 0.38 and 0.58, consistent with variation in carbon of major plant components. fOC followed a habitat gradient with lowest median values in Seagrass sediments (0.36 ± 0.09) and Permafrost habitats, followed by croplands (0.47 ± 0.08) and a maximum in semi-natural habitats (e.g., neutral, acid and calcareous grasslands) (0.56 ± 0.07), with differences between broadleaved (0.50 ± 0.087) and coniferous woodlands (0.53 ± 0.07) which were driven by overall organic matter content. The data show a tight link between vegetation carbon and the contents of SOC and SOM across various habitats, which could be used to inform agricultural soil management, improved land-use planning (e.g., woodlands), and tracking climate-related SOC targets.
Keywords: decomposition (biodegradation); humification; land use; loss-on-ignition; soil health; soil organic carbon; soil organic matter fractions; soil type